Penerapan Bauran Pemasaran 7P Pada Manarou Souvenir Di Kota Manado - Maramis, Rosalina Yohana; Waney, Nordy Fritsgerald Lucky; Katiandago, Theodora Maulina (AGRI-SOSIOEKONOMI, 2023)
This study aims to identify the application of the 7p marketing mix to Manarou Souvenir in the city of Manado. This research was conducted for 3 months from April to July 2023. The data used in this study were primary data and secondary data. Primary data obtained from direct interviews with business owners and consumers. Meanwhile, secondary data was obtained from literature and literature studies via the internet to access articles from various scientific journals and theses from other universities related to this research topic, particularly regarding Marketing Mix. The results of the study with the results of the analysis using a Likert scale on the Implementation of the 7P Marketing Mix in Manado City Manarou Souvenirs with an overall ideal score of 1.050 means that consumers agree that the 7P marketing mix has been implemented by Manarou Souvenirs.